2019
DOI: 10.1158/1538-7445.am2019-1446
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 1446: Characterization, evaluation and safety studies of the oncolytic Vaccinia virus TG6002 for canine cancer therapy

Abstract: Introduction: Oncolytic virotherapy with tumor selective viruses, such as Vaccinia viruses (VV), offers a promising treatment modality for cancer. TG6002 is a recombinant oncolytic VV deleted in two viral genes (thymidine kinase and ribonucleotide reductase) and armed with the suicide gene FCU1 that encodes a bifunctional chimeric protein which efficiently catalyses the direct conversion of the nontoxic 5-fluorocytosine (5-FC) into the toxic metabolite 5-fluorouracil (5-FU). Canine tumors are relevant predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…One study has already established the oncolytic potency of TG6002 with 5-FC in canine mammary tumor explants [13]. Histological analyses of ex vivo canine mammary adenocarcinoma explants cultured with TG6002 and 5-FC, allowed assessment of tumor necrosis and conversion of 5-FC into 5-FU [13]. Considering dogs as a relevant model in oncology, and the promising in vitro results combined with the safety pro le of TG6002 observed in the seven dogs in this study, intratumoral injections of 5 x 10 7 pfu/kg of TG6002 can be considered for clinical trial in dogs with spontaneous tumors.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…One study has already established the oncolytic potency of TG6002 with 5-FC in canine mammary tumor explants [13]. Histological analyses of ex vivo canine mammary adenocarcinoma explants cultured with TG6002 and 5-FC, allowed assessment of tumor necrosis and conversion of 5-FC into 5-FU [13]. Considering dogs as a relevant model in oncology, and the promising in vitro results combined with the safety pro le of TG6002 observed in the seven dogs in this study, intratumoral injections of 5 x 10 7 pfu/kg of TG6002 can be considered for clinical trial in dogs with spontaneous tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In this model, TG6002 in combination with 5-FC has signi cant antitumor e cacy against a large range of human tumors [11]. Another study has also showed relevant oncolytic features of TG6002 as an oncolytic therapy on canine cancer cell lines, mouse xenografts and canine mammary tumor explants [13]. Intratumoral injections of TG6002 in canine mammary tumor cells grafted onto mice lead to a signi cant decrease in tumor size [13].…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations